PENGEMBANGAN MEDIA BELAJAR BARET ARGEO BERBASIS ROLE PLAYING GAME TERHADAP MINAT BELAJAR SISWA - Faiz, Muhammad Ikhsan; Wibowo, Teguh; Darminto, Bambang Priyo (Math Educa Journal, 2021)
This research aims to establish a valid, practical, and effective media in the form of a game called Baret Argeo for students interest in learning at Senior High School 6 of Purworejo during online learning. This research is a development study that employs the ADDIE method (analysis, design, development, implementation, evaluation).A required analysis is carried out according to pandemic conditions during the analysis stage. The Baret Argeo design and components were produced during the design stage. Validation was carried out by content experts with a value of 3.93 (valid) and media experts with a value of 4.46 at the production level (very valid).which was then put to the test on 18 students in a practicality test with a score of 4.03 (very practical). Then the implementation of the 18 students used the Argeo Beret which was compared with the other 18 students who used the Student Worksheet (LKS) using the t test comparative analysis. The result is   with 4.4881> 2.0322 then  is rejected or it can be said that students' interest in learning using Beret Argeo is better than students using LKS. At the evaluation stage, the Argeo Beret is reserved to be used in a wider range of mathematics learning. This research has implications for students' interest in learning in the middle of distance learning.